A Study of Technology Innovation Affecting UAE Public Health Care Organisational performance - Abdulla, Ayesha Salem Mohammed Hassan; Al-shami, Samer Ali (Tropical Scientific Journal, 2023)
Objective: Innovative technology is critical for improving the UAE's healthcare performance. Healthcare professionals can streamline administrative chores, improve patient care, and reduce medical errors by incorporating modern technologies and systems. Technology-enabled solutions can also improve data analysis, facilitate evidence-based practices, and empower healthcare providers to provide more accurate diagnoses and personalized treatment strategies. Hence, this study was carried out to formulate a prediction multi-linear regression model of technology innovation dimensions affecting UAE public health care organizational performance. Research Method: Data was collected through a questionnaire survey among the employees of UAE public. A total of 398 completed questionnaire sets were used to formulate the equation model. Findings: It was found that the multi-linear regression equation model attained 0.529 degrees of fitness which is considered good. Originality: This equation model can be applied to measure the UAE public health care organizational performance by inserting the three variables’ values namely Organization Innovation Capabilities; Potential Absorptivity Knowledge; and Interaction with Technology. Hopefully, the outcomes of this research contribute to the body of knowledge and to the community of UAE public health care organizations